Techno Economic Modelling of Dried Black Potato (Plectranthus rotundifolius) - Ardi, Pradipta Risma Rukmana; Milzam, Muhammad; Ariwibowo, Didik; Paramita, Vita (Vocational College of Universitas Diponegoro, 2019)
The techno economic modeling of dried black potato (Plectranthus rotundifolius) was studied by employing electrical cabinet oven. The parameters investigated were including parameter obtained from analysis of capital budgeting, breakeven point and financial ratio of rentability. The obtained payback period was 2 years 11 months by investing 53.000.000 rupiah for machinery and 10.000.000 rupiah for start-up cost as initial capital. By assuming 10 years of dried black potato production, the value of net present value was equal to 1.207.982.611 rupiah. The value of gross profit margin and net profit margin were 0.97 and 0.87, respectively. Regarding to the positive value of net present value, the lower payback period value, and the high value of internal rate of return (74.47%) and also the profitability index (20.17), the modeling of techno economic was positively recommending the commercial application of dried black potato by using electrical cabinet oven.